PEMBUATAN ZAT WARNA ALAMI DARI BIJI KESUMBA DALAM BENTUK POWDER UNTUK MENDUKUNG INDUSTRI BATIK DI JAWA TENGAH - Paryanto Paryanto; Agus Purwanto (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2012)
Synthetic dyes are very practical to use and can lead to striking color on a colored product. This makes the synthetic dyes are often used in the food and beverage, pharmaceutical and textile. But the waste or residues of synthetic dyes can contaminate the environment than the use of synthetic dyes is often abused, such as the use of non synthetic food dyes in food products, thereby causing harm to consumers. Thus the natural dyes began to be reconsidered for use. Drawbacks of natural dyes extracted the natural dye is a liquid so it is not practical for long-term use. Dye is form in a liquid extract is dried into a powder by using a spray dryer. Extract natural dyes from kesumba seeds, mahogany bark and secang wood in this final assignment dried using a spray dryer that has been modified. In a spray dryer using a nozzle extracts scattered granules form small particles, granules - granules of small particles are contacted directly by the hot air that will be formed powder. Spray dryer consists of three main tools nozzle, dryer tank and cyclone. Nozzle is used to extract the dye waste so as to form granules of small particles. Tank made ​​of stainless steel dryer that has a diameter of 14 cm, height 94 cm, the maximum volume of 16 liter and 13 liter effective volume. Cyclone acts as a filter / separator between the dye powders with gaseous reaction products has a diameter of 16 cm and 64 cm high. Other support tools in the form of a compressor, blow dryer, and heater. Extract of mahogany and secang dye is obtained by solvent extraction to extract the water while the dye solvent kesumba extracted with 0.25% NaOH solution. Operation of the spray dryer by using semi-continuous system, with a continuous drying process in the tank while the bait into a maximum of 25 ml for each process with the average feed rate 0.13 ml / sec, can work well and can result in dye powder. Feed into the drying temperature to extract mahogany between 90-100 ° C, whereas for the extract of secang and kesumba between 100-110 ° C. This dye powder can then be used for dyeing textiles for dyeing cloth is batik.